Atmospheric Characterization of the Sub-Neptune Exoplanet K2-18b : a Bayesian Analysis of its Possible Structure and Composition (2025)
K2-18b is a temperate habitable-zone Sub-Neptune that has attracted significant interest due to its potential to host a H/He-rich envelope and to contain H2O traces in its atmosphere. Transmission spectroscopy with JWST has revealed the presence of the carbon-bearing molecules CH4 and CO2 along with the non-detection of NH3, aligning with the "Hycean" world scenario, which consists of a shallow H2-dominated atmosphere overlaying a potentially liquid water surface ocean, creating optimal conditions that favour habitability. Recent studies have proposed alternative scenarios compatible with observations, including a mini-Neptune scenario with a deep atmosphere and no well-defined surface, or a lava world scenario consisting of a molten magma ocean on its surface. Here, we report a Bayesian retrieval analysis of K2-18b’s transmission spectrum, exploring several models for its chemical composition, temperature profile, and cloud properties. We evaluate a set of not self-consistent atmospheric retrievals aiming to constrain the atmospheric properties, examining the detection significance of key molecular species and investigating how grey and non-grey cloud treatments impact the inferred structure and composition. For both cloud treatments, we find detection significances for CH4 and CO2 of 5 σ and 3 respectively, while finding no significant evidence for H2O and NH3, in agreement with previous studies. Additionally, we find that a cloud-free atmosphere for K2-18b is strongly ruled out by observations. Our results suggest that a model consisting of non-grey cloud treatment and following a semi-ideal temperature-pressure profile provides the best fit to the observed spectrum.